Seven new species of the genus Chrysolina Motschulsky from China (Coleoptera: Chrysomelidae: Chrysomelinae) - Ge, Si-Qin; Daccordi, Mauro; Li, Wen-Zhu; Yang, Xing-Ke (Zootaxa, 2011)
Seven new species of Genus Chrysolina Motschulsky are described: Chrysolina markamensis Daccordi et Ge, Chrysolina hohxilensis Daccordi et Ge, Chrysolina gyacaensis Daccordi et Yang, Chrysolina hongyuanensis Daccordi et Ge, and Chrysolina cuiae Ge et Daccordi, Chrysolina shuyongi Ge et Daccordi, Chrysolina zhangi Daccordi et Ge. Illustrations of habitus, male and female antennae, and male protarsi and aedeagus, and a map showing known localities are provided.